2014
DOI: 10.1007/s12032-014-0340-x
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to give anthracyclines concurrently with trastuzumab in neo-adjuvant or metastatic settings for HER2-positive breast cancer? A meta-analysis of randomized controlled trials

Abstract: Concurrent use of anthracyclines and trastuzumab used to be avoided in the treatment of HER2-positive breast cancer due to the high risk of cardiac toxicity. However, several newly published studies challenged this view and demonstrated that concomitant use of the two agents significantly improved the clinical outcome without causing additional cardiac toxicity. This meta-analysis summarized available data to investigate the safety and efficacy of concurrent use of anthracyclines and trastuzumab. Eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In addition, 2 patients received adjuvant treatment with a slightly different dosing schedule, and 4 patients were treated with the anti-HER2/neu antibody trastuzumab. Cardiac toxicity could be more serious when HER2/neu-targeting agents are combined with anthracyclines [28][29][30]. Our findings, however, are in line with a novel study showing that a combination of docetaxel with trastuzumab has no additional effect on the QT interval [31].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, 2 patients received adjuvant treatment with a slightly different dosing schedule, and 4 patients were treated with the anti-HER2/neu antibody trastuzumab. Cardiac toxicity could be more serious when HER2/neu-targeting agents are combined with anthracyclines [28][29][30]. Our findings, however, are in line with a novel study showing that a combination of docetaxel with trastuzumab has no additional effect on the QT interval [31].…”
Section: Discussionsupporting
confidence: 87%
“…However, when addressing toxicity, the authors observed that concurrent administration was indeed associated with significantly increased risk of cardiac-related adverse events. Subgroup analysis confirmed this finding both in the neoadjuvant and metastatic setting (Du et al, 2014). Currently, the use of trastuzumab concomitantly with an anthracyclinecontaining regimen is not recommended because of the potential for increased cardiotoxicity (Denduluri et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…This same regimen should be considered for elderly patients with a risk of taxane toxicity. Generically, combining anthracyclines with trastuzumab is not recommended, since it increases the risk of cardiotoxicity [52] If the patient relapses within the first 6 months after completing the trastuzumab adjuvant treatment, the first-line treatment with T-DM1 is recommended, since it has shown a median PFS and OS of 15.2–29.8 months, respectively, and appears to be less toxic than lapatinib combined with capecitabine [39, 53] (SEOM level of certainty: moderate; strength of recommendation: B).
Fig. 5Proposed treatment for patients with HER2-positive breast cancer
…”
Section: Treatment Option Recommendationsmentioning
confidence: 99%